Digital and Free Trade Zones Impact on Malaysia’s Economy and Its Prospects (2000–2018) - Midoun, Sissani; Ismail, Bengana (International Journal of Economics and Financial Issues, 2018)
Malaysia’s continue expanding its economy successfully and make great efforts as a leader in Southeast Asia. It has pursued a comparative equitable development path toward free trade zones (FTZ) and Digital trade zones (DFTZ) which will digitally gather users with government and business services to support cross-border trade as bring reforms to attract foreign funds and foreign direct investments. This paper aims show the intensive competition between countries on creating free zones as a form of integration. The second objective is to draw the attention of Malaysian authorities to invest heavily in free zones as modern form of economic diversification. Keywords: Export processing zones, diversification, economic integration, attractiveness. JEL Classifications: F20; F21; F23